How Far Has Our Wakaf Been Researched? - Aam Slamet Rusydiana; Salman Al Farisi (Faculty of Economic and Business, 2016)
In practice, waqf in Indonesia faces many hard problems, because commonly known as non-productive waqf. Talking about waqf, it’s not only as religious rituality but also could touch humanity aspect by empowering its potency to maximize public wealth. On the other hand, the research related to waqf is still very lack, but it is very important to do. This study reviews on research around waqf. The study used descriptive statistical analysis based on 100 journal publications related to waqf, both national and international journal. The entire sample journal publications have published last 5 years from 2011 to 2015. Results show that the waqf research is still dominated by the discussion of non-cash waqf (62%) then the cash waqf (38%). This gives a general overview for researchers to produce better research related to cash waqf. In addition, comparison of quantitative research methods is still far less than the qualitative approach.DOI: 10.15408/etk.v15i1.3110